2019
DOI: 10.1155/2019/8503962
|View full text |Cite
|
Sign up to set email alerts
|

Discovering Travel Community for POI Recommendation on Location‐Based Social Networks

Abstract: Point-of-interest (POI) recommendations are a popular form of personalized service in which users share their POI location and related content with their contacts in location-based social networks (LBSNs). The similarity and relatedness between users of the same POI type are frequently used for trajectory retrieval, but most of the existing works rely on the explicit characteristics from all users’ check-in records without considering individual activities. We propose a POI recommendation method that attempts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Recommendation system is an important information filtering method at present, among which collaborative filtering (CF) is widely used in large-scale recommendation engines due to its high efficiency, accuracy and scalability [6]. CF can be roughly divided into three categories: the model-based [7], the memory-based [8] and the context-based [16].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Recommendation system is an important information filtering method at present, among which collaborative filtering (CF) is widely used in large-scale recommendation engines due to its high efficiency, accuracy and scalability [6]. CF can be roughly divided into three categories: the model-based [7], the memory-based [8] and the context-based [16].…”
Section: Related Workmentioning
confidence: 99%
“…The results indicated that the method outperformed several conventional tag-based methods. To alleviate the sparsity for new and inactive users, Tang et al [16] proposed a POI recommendation method which attempts to recommend best POI types to multiple users. The purpose of this method is to predict the target POIs of users and search similar users with the same interest, so as to optimize the user acceptance rate of each recommendation.…”
Section: B Recommendation Based On Social Networkmentioning
confidence: 99%
“…POI recommendation is one of hot topics and it can provide better POIs for route planning. Lei Tang [22] et al proposed a personal POI recommendation method based on destination prediction. And Jianxin Li [23] proposed Personalized Influential Topic Search, or more succinctly PIT-Search.…”
Section: Related Workmentioning
confidence: 99%
“…After that, we add the keyword to the result set and assign the result set to pre set (lines [14][15][16][17]. After the initial step, the algorithm finds the service with lower priority through the last finished service and stores the service into the result set (lines [19][20][21][22][23][24][25][26][27][28]. Finally, the algorithm outputs the result set (line 29).…”
Section: Priority Querymentioning
confidence: 99%
“…With the maturity of internet technology and the widespread application of global satellite positioning systems, locationbased social network (LBSN) has gradually received more and more attention and research. Recommending future potential points of interest (POI) to users by analyzing their existing historical check-in points has become a research hotspot in this field [1]. Specifically, personalized POI recommendation tasks can be divided into two types according to the recommendation basis.…”
Section: Introductionmentioning
confidence: 99%